Cities and the wealth of nations: How can Helsinki, London, Paris and Stockholm prosper from TTIP? - Fredrik Erixon; Martina Francesca Ferracane (European Centre for International Political Economy (ECIPE), 2014)
The two major forces shaping the global economy are globalisation and urbanisation. Both these forces have both contributed to a much greater role of global cities for the way an economy is structured. A global city is a large city but not necessarily a mega city - a city defined by the size of its population alone. Size is important to build agglomerative strengths, but the defining character of a global city is rather its capacity to help reinforce the mechanics of specialisation and division of labour in the economy. (...) This study contextualises trade policy in four global cities in Europe: Helsinki, London, Paris and Stockholm. They are in several ways different, but they share one character: they are cities that spur specialisation in a larger economy. Even "small" cities like Helsinki and Stockholm play that role - and increasingly so as adaptation to data and the modern digital sector have become competitive strengths (or weaknesses) for a larger region. While London and Paris can utilise their size to achieve agglomerative effects in capital and labour, a city like Stockholm does it by serving the larger Nordic region and by stronger reliance on qualitative characters of specialisation. (...)
Keywords: 330